The Analysis of Volleyball Learning and Its Impact on Physical Fitness: A Longitudinal Review of Speed, Strength, and Flexibility in the Perspective of the Sport Pedagogy Approach to Physical and Health Education - Agung Wahyudi; Bambang Priyono; Sandey Tantra Paramitha; Bayu Murti Suryonegoro; Akbar Kusuma Abadi; Supriyono Supriyono; Ayu Tisa Rizqanada; Ricko Irawan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The importance of physical fitness in volleyball and its application in physical education which has not been maximized has encouraged research on the analysis of the impact of physical fitness on volleyball learning in relation to a longitudinal review of the aspects of speed, strength, and flexibility from the perspective of a sports pedagogy approach. Methodology: This study uses a longitudinal approach to analyze changes in aspects of learning evaluation and physical fitness of students over a period of 24 weeks involving three main parameters, namely: strength, speed, and flexibility through test instruments, to then be analyzed using repeated measurements of one factor (ANOVA) and measuring effect size with Hedges' g. Main Findings: The results of the study revealed that volleyball learning has a positive impact on students' learning achievement patterns and physical fitness in terms of speed, strength, and flexibility viewed from sports pedagogy. The implications of these findings are relevant to the development of physical education curricula and sports training programs along with their assessments that provide a scientific basis for planning sustainable training programs. Novelty/Originality of this study: The analysis of volleyball learning and its impact in the field of physical education evaluation in this study focuses on analyzing the sports pedagogy approach so that it not only analyzes the impact of learning but also develops an analysis related to aspects of physical fitness and learning as a whole using a longitudinal review from a sports pedagogy perspective.